A study of social-emotional adjustment levels of preschool children in relation to peer relationships - (:unkn) unknown (My University, 2013)
The aim of this research is to study social-emotional adaptation levels of 5- to 6-year old preschool children in relation to peer relationships. One hundred and forty-four children aged between 5 and 6 joined in this relational survey study. According to the results of the research analysing the relationship between the social-emotional adjustments of 5- to 6-year old children continuing preschool education and the peer relationship variables; the social-emotional adjustment level can meaningfully predict the prosocial behaviour of children towards their peers, aggression levels and exclusion by peers, fear-anxiety towards peers, hyperactivity-distractibility and peer victimisation. © 2013 © 2013 ASPE.
Keywords: peer relationships; preschool children; social-emotional adjustment; victimisation